Added values of the local timbers materials for main bridge frame structures utilizing laminating composites technology - Ari Sandhyavitri; Fakhri Fakhri; Rizki Ramadhan Husaini; Indra Kuswoyo; Manyuk Fauzi (Journal of Applied Materials and Technology, 2020)
The objectives of this article are to seek the opportunity to enhance the local Indonesia timber material physical performances (encompassing the low-class quality of III and IV timbers with the Modulus of Elasticity (MOE) = 5,000 - 9,000 MPa) utilizing laminated composite technology to become higher-class timber quality (class II) with the Modulus of Elasticity (MOE)> 15,000 MPa so that it can be used as an alternative material for constructing the bridge mainframe structures (girder beams) especially for the Indragiri Hilir regency, Riau Province, Indonesia. This regency needs several hundred small-medium bridges for connecting 20 districts, 39 wards, and 197 villages using local materials such as local timbers. This laminating technology is not a new technology but the utilization of this technology for constructing the main bridges structures is challenging and limited to the implementation in the civil construction industrial sector. This study composed 2 types of the low-class quality (lcq) of timber materials (such as Shorea sp and Shorea peltata Sym) and 2 types of medium class-quality (mcq) ones (Dipterocarpus and Calophyllum) for constructing the main bridge structures. Based on the laboratory test results utilizing 80% of lcq materials and 20% mcq ones, these composite timber materials may increase the timbers MOE by 145% to 166% from the existing MOE value of the mcq solid timbers. Based on the simulations these laminated composites wooden bridge girders 2 x (70x20) m2, these timber materials have passed all the tests and the application of this technology may improve the lcq timber values and it could be used for an alternative material of the bridge girder's main structures.